Chemically induced stresses in the cathode of single chamber solid oxide fuel cell - Zolochevsky, A.; Tkachuk, N. N.; Viricelle, J.-P.; Pijolat, C. (НТУ "ХПИ", 2007)
A relation between diffusion of the oxygen ions, chemical expansion in electrochemical ceramics, and chemically induced stress evolution in the cathode over time for the Single Chamber Solid Oxide Fuel Cell based on the miniaturisation concept using thick films produced by screen-printing method has been established. The proposed model has been used to calculate the time dependent stress distribution in the cathode as a function of the material parameters, geometrical parameters of the cathode, and concentration of the oxygen ions under steady state operating conditions of the Single Chamber Solid Oxide Fuel Cell.

Установлено зв’язок між явищами дифузії іонів кисню, хімічним розширенням в електрохімічній кераміці та розвитком хімічно наведених напружень в часі в катоді твердооксидних паливних елементів з одним стеком мініатюрної конфігурації на базі тонких плівок у формі печатних плат. Розроблену модель використано для розрахунків залежних від часу розподілень напружень в катоді як функцій фізичних параметрів матеріалу, геометричних параметрів катоду та концентрації іонів кисню в сталих умовах роботи твердооксидних паливних елементів з одним стеком.
Keywords: електрохімічна кераміка; дифузія; хімічне розширення; параметри катоду; твердооксидні паливні елементи; напруження